Virtual public opinion and public policies in Algeria - زنوحي محمد الأمين; رايس علي ابتسام (International Journal of Social Communication, 2022)
With the continuous development and progress of social economy, science and technology, Internet technology has developed in the world. Where the popularization and application of the Internet brought great convenience to people, enhanced communication and interaction between governments and peoples, and increased new ways of expressing public opinion; Governments have given an important role in gathering social opinions on the Internet. Public opinion also encourages democratization and rationalization of public policiesIn this research paper, we will discuss a number of essential points related to focusing on public opinion in general and clarifying its functions and technical factors affecting it, then talking about the importance of public opinion in the media and politics, as well as addressing virtual public opinion as an important axis in this study and highlighting its characteristics that emerged with the emergence of the Internet and its development More with social interaction sites and blogs.